Water‐Insensitive Electron Transport and Photoactive Layers for Improved Underwater Stability of Organic Photovoltaics (Adv. Funct. Mater. 40/2022). (5th October 2022) - Lin, Chieh‐Ting; Hsieh, Cheng‐Tien; Macdonald, Thomas J.; Chang, Jia‐Fu; Lin, Po‐Chen; Cha, Hyojung; Steier, Ludmilla; Wadsworth, Andrew; McCulloch, Iain; Chueh, Chu‐Chen; Durrant, James R
Abstract : Organic Photovoltaics In article number 2203487, Chieh‐Ting Lin, Chu‐Chen Chueh, and co‐workers systematically investigate the water‐immersion stability among a series of organic donors/acceptors and electron transporting layers. This work presents a strategy to develop water‐insensitive organic photovoltaics by combining the use of a nanoparticle titanium dioxide electron transporting layer and all‐polymer bulk heterojunction blends, which shows stable morphology and charge transfer kinetics after water immersion.